Evolution of Fatty Liver Disease and Relationship With Lipoproteins and Clinical Outcomes in Hepatitis B/Human Immunodeficiency Virus Coinfection. (26th October 2021) - Khalili, Mandana; King, Wendy C; Kleiner, David E; Chung, Raymond T; Bhan, Atul K; Ghany, Marc G; Sulkowski, Mark S; Lisker-Melman, Mauricio; Jain, Mamta K; Janssen, Harry L A; Hinerman, Amanda S; Sanyal, Arun J; et al.
Abstract : Fatty liver disease status did not significantly change in most hepatitis B virus/HIV–coinfected patients across 3–4 years. Patients with unfavorable lipid and lipoprotein profiles at baseline may have an increased risk for cardiovascular disease. Abstract: Background: Fatty liver disease (FLD) and hepatitis B virus (HBV) infection occur commonly in human immunodeficiency virus (HIV). FLD resolution is associated with improvement in lipoproteins in HIV-uninfected patients. We evaluated changes in FLD in an HBV/HIV-coinfected cohort. Methods: One hundred eight HBV/HIV-coinfected adults with baseline liver biopsies were followed every 24 weeks (median, 166 weeks) and 60 had follow-up biopsies. Baseline FLD categories (none, ≥5% steatosis, steatohepatitis), their change, and relationships with clinical and lipid/lipoprotein parameters were explored using multivariable modeling. Results: Median age was 50 years, and 93% were male. At baseline 30% had FLD. With control for lipid-lowering medications and body mass index, low-density lipoprotein (LDL) cholesterol (LDL-C), LDL particle concentration (LDL-P), and apolipoprotein B (apoB) decreased and adiponectin increased over time (all P < .05); On follow-up (vs baseline), there was no significant difference in FLD category ( P = .85); 60% remained without FLD, 17% had unchanged, 12% worsening, and 12% improved FLD. Baseline low-density lipoproteins (LDL-C, LDL-P, small LDL-P) and apoB appeared highest in those with unchanged FLD status (all P < .05). No associations between changes in FLD across follow-up (worsening/improvement vs unchanged) and lipid/lipoproteins changes were identified. Conclusions: In this cohort, there was no significant change in FLD prevalence over a relatively short timeframe. Baseline atherogenic lipids appeared highest in those with persistent steatosis or steatohepatitis, suggesting potentially increased cardiovascular risk in this group, but an independent relationship between individual-level change in FLD status and lipid/lipoprotein levels across follow-up was not observed.